Penetapan Harga Eceran Tertinggi Minyak Goreng Perspektif Maslahah Mursalah Analisis Peraturan Menteri Perdagangan Nomor 49 Tahun 2022 Tentang Tata Kelola Minyak Goreng Rakyat - Mhd. Chairul Ikhsan,; Cahaya Permata, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
One of the important needs for the Indonesian people is cooking oil. Inflation is one way cooking oil supports the Indonesian economy. Therefore, policies that support it must be supported by policies that can improve the lives of many people, such as pricing, shipping goods, and maintaining market price stability. Permendag No. 49 of 2022 article 10 paragraph 2, which regulates the management of people's cooking oil of IDR 14,000.00 per liter or IDR 5,500.00 per kilogram for people's cooking oil in bulk and IDR 14,000.00 per liter for premium packaged cooking oil. This study aims to determine how Indonesia regulates the highest retail price of cooking oil, the impact of setting the highest retail price on the community, and an analysis of Permendag No. 49 of 2022 concerning the highest retail price of cooking oil from a maslahah mursalah perspective. By using the conceptua approach and statute approach, this research is normative. Document studies are used to collect legal documents, which are then processed and reviewed descriptively using deductive reasoning logic. This study shows that the retail price policy for cooking oil causes punic buying in the community, because it causes cooking oil stocks to run low and creates competition between traditional and modern traders. This policy is known as maslahah ammah, which is believed to have a good impact in providing protection to consumers and buyers.